Human cardiac progenitor cells with regenerative potential can be isolated and characterized from 3D-electro-anatomic guided endomyocardial biopsies. (15th August 2017) - D'Amario, Domenico; Leone, Antonio Maria; Narducci, Maria Lucia; Smaldone, Costantino; Lecis, Dalgisio; Inzani, Frediano; Luciani, Marco; Siracusano, Andrea; La Neve, Federica; Manchi, Melissa; Pelargonio, Gemma; Perna, Francesco; et al.
Abstract: Aims: In the present study, we aimed to develop a percutaneous approach and a reproducible methodology for the isolation and expansion of Cardiac Progenitor Cells (CPCs) from EndoMyocardial Biopsies (EMB) in vivo . Moreover, in an animal model of non-ischemic heart failure (HF), we would like to test whether CPCs obtained by this methodology may engraft the myocardium and differentiate. Methods and results: EMB were obtained using a preformed sheath and a disposable bioptome, advanced via right femoral vein in 12 healthy mini pigs, to the right ventricle. EMB were enzymatically dissociated, cells were expanded and sorted for c-kit. We used 3D-Electro-Anatomic Mapping (3D-EAM) to obtain CPCs from 32 patients affected by non-ischemic cardiomyopathy. The in vivo regenerative potential of CPCs was tested in a rodent model of drug-induced non-ischemic cardiomyopathy. c-kit positive CPCs replicative capacity was assessed in 30 patients. Telomere length averaged 7.4 ± 0.4 kbp and telomerase activity was present in all preparations (1.7 × 10 5 copies). The in situ hybridization experiments showed that injected human CPCs may acquire a neonatal myocyte phenotype given the expression of the alpha-sarcomeric actin together with the presence of the Alu probe, suggesting a beneficial impact on LV performance. Conclusions: The success in obtaining CPCs characterized by high regenerative potential, in vitro and in vivo, from EMB indicates that harvesting without thoracotomy in patients affected by either ischemic or non-ischemic cardiomyopathy is feasible. These initial results may potentially expand the future application of CPCs to all patients affected by HF not undergoing surgical procedures.